Sistem Monitoring Tanaman Cabai untuk Meningkatkan Hasil Panen - Haris Supriatna; Titi Widaretna; Jajat Sudrajat (LPPM STMIK Mardira Indonesia, 2022)
A chili plant monitoring system has been created to increase crop yields, this system monitors soil pH and soil moisture in order to increase the growth of chili plants so that the yield obtained is maximum. This system uses Arduino UNO as its microcontroller with output in the form of automatic plant watering and automatic fertilizer. Important variables to support plant growth are soil moisture, soil pH, and the right watering time and duration. Measurement of soil pH and soil moisture is carried out using soil moisture sensor and soil pH sensor. While the output produced from the water pump and fertilizer and servo motor as the control. The measurement results of the two sensors will then be displayed on the LCD (Liquid Crystal Display). The test results of soil pH monitoring tools and soil moisture in chili plants show measurement results with good accuracy. The measurement results have been successfully displayed on the LCD, as well as the pump ejects automatically and the servo controls automatically.